1999
DOI: 10.1002/(sici)1521-4095(199901)11:1<61::aid-adma61>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for the Synthesis of Tin / Tin Oxide Nanoparticles of Low Size Dispersion and of Nanostructured SnO2 for the Sensitive Layers of Gas Sensors

Abstract: 30] Note the reversal of the hydrophilic±hydrophobic character of the two surface regions on going from operation 2 to operation 4 (Fig. 2).[31] a) [32] The role of atmospheric humidity in this tip-induced surface oxidation (by analogy with previously reported processes of scanning-probe anodization [26,33]) remains to be elucidated.[35] As suggested by the spectroscopic data and additional chemical derivatization experiments, NTS eo generated in this manner appears to be the enolate of a hydroxy carbonyl (ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 8 publications
2
111
0
2
Order By: Relevance
“…[26][27][28][29][30][31][32][33] We have shown that this methodology can be extended to the synthesis of nanoparticles of metal oxides with a precise control of morphology. [34][35][36][37] which can be, in a second step, oxidized into well crystallized nanoparticles of the corresponding oxides, without coalescence. We recently reported a direct organometallic route to prepare ZnO colloidal solutions containing nanoparticles of controlled size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] We have shown that this methodology can be extended to the synthesis of nanoparticles of metal oxides with a precise control of morphology. [34][35][36][37] which can be, in a second step, oxidized into well crystallized nanoparticles of the corresponding oxides, without coalescence. We recently reported a direct organometallic route to prepare ZnO colloidal solutions containing nanoparticles of controlled size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nayral et al [6] proposed an interesting route to synthesize nanometer-size SnO 2 particles, based on the oxidation of Sn 0 nanoparticles. The tin nanoparticles were prepared by controlled decomposition of an organometallic precursor such as [Sn(NMe 2 ) 2 ] 2 .…”
mentioning
confidence: 99%
“…Entre os métodos mais empregados podem ser citadas a co-precipitação, sol-gel, condensação de fase gasosa, spray-pirólises, microemulsão, microondas, oxidação de Sn 0 , precursor polimérico e rotas hidrotérmicas, entre outras [47][48][49][50][51][52][53][54][55] . A co-precipitação e o sol-gel são geralmente preferidos pela facilidade de execução e bons resultados obtidos.…”
Section: Nanopartículasunclassified